2016
DOI: 10.1111/gcbb.12350
|View full text |Cite
|
Sign up to set email alerts
|

Phenomics analysis of drought responses in Miscanthus collected from different geographical locations

Abstract: Miscanthus is a genus of C4 perennial grasses capable of high biomass potential even in temperate regions making it an ideal industrial crop for the renewable supply of energy and chemicals. Yield is strongly linked to water availability, and many environments have limited water supply where otherwise irradiation and temperature are favourable. A total of 47 Miscanthus genotypes, diverse regarding collection site and genotype, were screened in a high-throughput phenomics facility under drought to generate high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 83 publications
3
37
3
Order By: Relevance
“…Extensive environmental measurements of soil and climate, combined with growth monitoring, are being used to understand abiotic stresses (Nunn et al, ; Van der Weijde, Huxley, et al, ) and develop genotype‐specific scenarios similar to those reported earlier in Hastings et al (). Phenomics experiments on drought tolerance have been conducted on wild and improved germplasm (Malinowska, Donnison, & Robson, ; Van der Weijde, Huxley, et al, ). Recently produced interspecific hybrids displaying exceptional yield under drought (~30% greater than control Mxg ) in field trials in Poland and Moldova are being further studied in detail in the phenomics and genomics facility at Aberystwyth to better understand gene–trait associations which can be fed back into breeding.…”
Section: Miscanthusmentioning
confidence: 99%
“…Extensive environmental measurements of soil and climate, combined with growth monitoring, are being used to understand abiotic stresses (Nunn et al, ; Van der Weijde, Huxley, et al, ) and develop genotype‐specific scenarios similar to those reported earlier in Hastings et al (). Phenomics experiments on drought tolerance have been conducted on wild and improved germplasm (Malinowska, Donnison, & Robson, ; Van der Weijde, Huxley, et al, ). Recently produced interspecific hybrids displaying exceptional yield under drought (~30% greater than control Mxg ) in field trials in Poland and Moldova are being further studied in detail in the phenomics and genomics facility at Aberystwyth to better understand gene–trait associations which can be fed back into breeding.…”
Section: Miscanthusmentioning
confidence: 99%
“…A growth model was developed and refined that takes meteorological and soil data as input and estimates yield at a spatial resolution of 1 ha. This model was largely developed and parameterised with data from field trials growing M × g. Controlled environments and field experiments have demonstrated that M × g is sensitive to drought stress in particular, but also chilling stress and that accessions that yield more under abiotic stress have been identified [23,24]. Thus there is identified genetic potential for improvements over the current commercial standard in particular stressed environments.…”
Section: Phenotyping In Multi-location Plot Trialsmentioning
confidence: 99%
“…Leveraging economies of scale and using standardised procedures, high-throughput phenotyping screens addresses these challenges and have been applied in biological screening of chemical compound libraries, agricultural evaluation of crop plants, genome-wide CRISPR-based mutagenic cell line screens and multi-centre phenotypic screening of mutated model organisms [6][7][8][9][10][11][12][13] . The continuous generation of large volumes of data introduces new challenges affecting automated approaches to statistical analysis that have to scale with increasing data and address the underlying complexity inherent in large projects [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%